Workers and the Right in Spain, 1900-1936 - Winston, Colin M., 1955- (Book collections on Project MUSE., 1985)
Colin Winston traces the Libres' emergence following the collapse of Catholic syndicalism in Catalonia and shows how, in the period up to the Civil War, they moved from radical Carlism to a form of proletarian fascism.Originally published in 1984.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.